Association between dietary inflammatory index (DII) and insulin resistance (HOMA-IR) in obese adults - Millennia Dorais Sinaga; Ninik Rustanti (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
The global rise in obesity, including in Semarang, Indonesia, has been associated with an increased risk of insulin resistance, which can be assessed using the Homeostatic Model Assessment for Insulin Resistance (HOMA-IR). Diet plays a crucial role in modulating systemic inflammation. The Dietary Inflammatory Index (DII) is a validated tool used to quantify the inflammatory potential of dietary intake. However, few studies have explored the relationship between the ((DII) and HOMA-IR in obese individuals. This study aimed to analyze the association between DII score and HOMA-IR in obese adults in Semarang City. A cross-sectional study was conducted from September to November 2024, involving 66 obese adults aged 26–50 years (Body Mass Index [BMI] ≥25 kg/m²), selected through purposive sampling. Dietary intake was assessed using a semi-quantitative food frequency questionnaire (SQ-FFQ), and DII scores were calculated based on established algorithms. Fasting Blood Glucose (FBG) and fasting insulin levels were measured to calculate HOMA-IR. Data analysis was performed using Pearson’s correlation and multiple linear regression adjusted for age and BMI. A DII score > 0 indicated a pro-inflammatory diet and HOMA-IR values >2,0, indicating insulin resistance. The results showed a significant positive association between the DII score and HOMA-IR (p = 0,002). Multiple regression analysis showed that the DII remained a significant predictor of HOMA-IR after adjusting for age and BMI (Model 1: β = 0,362, p = 0,007; Model 2: β = 0,381, p = 0,002; Model 3: β = 0,368, p = 0,002). The final model explained 24,3% of the variance in HOMA-IR (R² = 0,243), indicating a moderate effect size. In conclusion, a higher Dietary Inflammatory Index score was significantly associated with increased insulin resistance among obese adults in Semarang, independent of age and BMI. These findings highlight the potential role of diet-induced inflammation in metabolic dysregulations.